A high wear-resistant hard alloy material and preparation method thereof
Through ball mill modification and sintering improvement processes, combined with graphene-modified strong agent and lanthanum-regulated chitosan liquid, the problem of difficult to coordinate the wear resistance and fracture toughness of cemented carbide materials is solved, and its performance stability in various environments is significantly improved.
Patent Information
- Application Number
- CN202410669990.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-28
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-05-28
AI Technical Summary
The wear resistance and fracture toughness of existing cemented carbide materials are difficult to coordinately improve, and the stability of hot and cold shocks and acid and corrosion resistance is poor, which limits the efficiency of the product.
The cemented carbide powder is modified by ball milling liquid, and the extrusion molding and sintering improvement process is used to form a cemented carbide material with high wear resistance. Cemented carbide powder consists of tungsten carbide, niobium carbide and nickel powder, and the ball abrasive liquid consists of graphene-modified strong agent and lanthanum-regulated chitosan liquid.
It significantly improves the wear resistance and fracture toughness of cemented carbide materials, and enhances its stability under hot and cold impact and acid-corrosion resistance conditions, improving the efficiency of the product.
Smart Images

Figure BDA0004862378920000141 
Figure BDA0004862378920000151 
Figure BDA0004862378920000161
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cemented carbide, and in particular to a high-wear-resistant cemented carbide material and a preparation method thereof. Background Art
[0002] Cemented carbide is an alloy material made from hard compounds of refractory metals and bonding metals through powder metallurgy. It has the characteristics of high hardness, good wear resistance and good red hardness at high temperatures. It is widely used in national economic fields such as cutting, mining, infrastructure, as well as military, nuclear energy, aerospace and other national defense and military industries.
[0003] The existing cemented carbide uses simple raw materials and existing sintering process. The resulting cemented carbide has poor wear resistance and low fracture toughness. It is difficult to coordinate and improve the wear resistance and fracture toughness of the product. In addition, the product has poor thermal shock and acid corrosion resistance, which limits the product's use efficiency. Summary of the invention
[0004] In view of the defects of the prior art, the object of the present invention is to provide a high wear-resistant cemented carbide material and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution:
[0006] The present invention provides a high-wear-resistant cemented carbide material. The cemented carbide material is prepared by ball-milling cemented carbide powder and ball-milling liquid in a weight ratio of (5-7):2 to form a ball-milled modified body. The ball-milled modified body is then extruded and sintered to obtain the cemented carbide material.
[0007] The cemented carbide powder includes the following raw materials by weight: 30-35 parts of tungsten carbide, 5-10 parts of niobium carbide, and 2-4 parts of nickel powder;
[0008] The ball milling liquid comprises the following raw materials in parts by weight: 10 to 15 parts of a bonding agent based on graphene modification and 8 to 12 parts of a lanthanum-regulated chitosan liquid.
[0009] Preferably, the preparation method of the graphene-modified bonding agent is:
[0010] S01: The graphene is first placed in a 10% potassium permanganate solution with a mass fraction of 3 to 5 times the total amount of graphene, mixed thoroughly, then diluted with water, dried, and set aside;
[0011] S02: The graphene product of S01 and the nano-silicon dioxide modified liquid are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is washed with water, filtered and dried to obtain a graphene agent with continuous effect of silicon dioxide;
[0012] The preparation method of nano-silicon dioxide modified liquid is as follows:
[0013] First, the nano-silicon dioxide is added into a sodium silicate solution which is 3 to 5 times the total amount of the nano-silicon dioxide, and stirred and mixed thoroughly, and then filtered and dried to obtain the nano-silicon dioxide agent;
[0014] 2 to 5 parts of nano-silicon dioxide and 1 to 3 parts of stearic acid are added to 4 to 7 parts of phosphate buffer solution, and then 2 to 4 parts of sodium alginate are added and mixed to obtain a nano-silicon dioxide modified solution;
[0015] S03: The silica-modified graphene agent and the strengthening agent are mixed and ball-milled in a weight ratio of 5:3, with a ball-milling speed of 1000-1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a graphene-modified strengthening agent.
[0016] Preferably, the stirring temperature of the stirring modification treatment is 48-52° C., the stirring speed is 550-750 r / min, and the stirring time is 1-2 h.
[0017] Preferably, the mass fraction of the sodium silicate solution is 10-15%; and the pH value of the phosphate buffer solution is 5.5.
[0018] Preferably, the emphasizing agent comprises the following raw materials in parts by weight:
[0019] 4-7 parts of nano strontium titanate, 1-3 parts of carboxymethyl cellulose, 5-8 parts of 10% sodium lignin sulfonate solution by mass, 1-2 parts of nano silica sol and 1-2 parts of 5% cobalt nitrate solution by mass.
[0020] Preferably, the preparation method of the lanthanum-regulated chitosan solution is:
[0021] S101: irradiating the silicon carbide whisker with protons for 5 to 10 minutes at an irradiation power of 350 to 400 W, and obtaining irradiated silicon carbide whiskers after the irradiation is completed;
[0022] S102: chitosan is added to a sodium dodecylbenzene sulfonate solution at a weight ratio of 2:5, and then a lanthanum chloride solution with a total amount of 5-10% of the total amount of chitosan, an irradiated silicon carbide whisker with a total amount of 8-12% of the total amount of chitosan, and a silane coupling agent KH560 with a total amount of 2-5% of the total amount of chitosan are added, and the mixture is continued to be fully mixed to obtain a lanthanum-adjusted chitosan solution.
[0023] Preferably, the mass fraction of the sodium dodecylbenzene sulfonate solution is 8-12%; the mass fraction of the lanthanum chloride solution is 2-5%.
[0024] Preferably, the specific process of the sintering improvement is:
[0025] The sintering temperature is first raised to 70-75°C at a rate of 1-3°C / min, and then immersed in an yttrium nitrate solution for ultrasonic immersion treatment. After the immersion is completed, the sintering is taken out;
[0026] The sintering temperature is then raised to 450-480°C at a rate of 2-5°C / min and sintered for 5-10 minutes;
[0027] Then, the temperature is raised to 1050-1100°C at a rate of 8-12°C / min and sintering is continued for 25-30min;
[0028] Then increase the temperature to 1470-1490°C at a rate of 1-3°C / min, continue to keep warm for 10-15 minutes, and finally air cool to room temperature.
[0029] Preferably, the immersion power of the ultrasonic immersion treatment is 400-450W, and the immersion time is 20-25min; the mass fraction of the yttrium nitrate solution is 2-5%.
[0030] The present invention also provides a method for preparing a high wear-resistant cemented carbide material, comprising the following steps:
[0031] Step 1, the raw materials of cemented carbide powder are mixed uniformly according to the proportion to obtain cemented carbide powder; then the cemented carbide powder and the ball milling liquid are ball milled at a weight ratio of (5-7):2, the ball milling speed is 1500r / min, the ball milling is performed for 2h, and after the ball milling is completed, the ball milling is washed with water and dried to form a ball milled modified body;
[0032] Step 2: Extruding the ball-milled modified body in a molding machine at a pressure of 100-120 MPa for 20-30 min to obtain a molded body, and finally sintering and improving the body to obtain the high wear-resistant cemented carbide material of the present invention.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] 1. The cemented carbide material of the present invention adopts cemented carbide powder to be ball-milled and modified by ball-milling liquid, and then extruded and sintered to obtain the alloy material. The tungsten carbide, niobium carbide and nickel powder in the cemented carbide powder are blended and prepared, and then ball-milled and improved by a ball-milling liquid composed of a graphene-modified bonding agent and a lanthanum-adjusted chitosan liquid. The graphene-modified bonding agent and the lanthanum-adjusted chitosan liquid are used to coordinate and work together, so that the fracture toughness and wear resistance of the product are coordinated and improved, and the acid corrosion resistance and thermal shock stability of the product are significantly improved. In addition, the sintering improvement treatment of the present invention is combined to further improve the performance of the product.
[0035] 2. The graphene-modified continuous strengthening agent adopts graphene activated and oxidized by potassium permanganate to optimize the active efficiency of graphene, and at the same time, it is coordinated and modified by nano-silicon dioxide modified liquid. The nano-silicon dioxide in the nano-silicon dioxide modified liquid is first coated and improved by sodium silicate solution, and then coordinated and matched with stearic acid, phosphate buffer solution, and sodium alginate. Through the mutual coordination and synergy between the raw materials, the graphene is further improved, and the graphene body is enhanced with nano-silicon dioxide with a high specific surface area, so that the ball milling liquid is optimized in the graphene distribution system to improve the interface of the alloy powder raw material, and the performance effect of the alloy body is enhanced. At the same time, the strengthening agent adopts nano-strontium titanate, carboxymethyl cellulose, sodium sulfonate solution, nano-silica sol and 5% cobalt nitrate solution by mass fraction. Nano-strontium titanate is matched with cobalt nitrate solution, and the coordination and matching between the raw materials are adopted to further enhance the coordination and synergy effect of the continuous-effect graphene agent of silica, so that the performance effect of the product is further enhanced;
[0036] 3. Lanthanum-regulated chitosan liquid uses silicon carbide whiskers to be irradiated with protons to stimulate the activity of the whiskers, and then chitosan, sodium dodecylbenzene sulfonate solution, lanthanum chloride solution and silane coupling agent KH560 are mutually adjusted and adjusted, and the whisker structure is coordinated with lanthanum to adjust the raw materials in the chitosan liquid to adjust the mutual effects, enhance the interface of the raw materials of the system product, and enhance the coordinated improvement of the wear resistance and fracture toughness of the product. At the same time, the acid corrosion resistance and cold and hot shock resistance of the product are further improved;
[0037] 4. In the sintering improvement treatment, the temperature is first raised to 70-75°C at a rate of 1-3°C / min, and then immersed in an yttrium nitrate solution for ultrasonic immersion treatment. The yttrium nitrate solution is used to optimize the activity efficiency of the alloy body grains. At the same time, the product is subjected to the staged sintering of the present invention, the grains are refined, and the grain structure is strengthened, so that the performance coordination and performance stability of the product are further improved. DETAILED DESCRIPTION
[0038] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] A high wear-resistant cemented carbide material of this embodiment is obtained by ball-milling a cemented carbide powder and a ball-milling liquid in a weight ratio of (5-7):2 to form a ball-milled modified body, and the ball-milled modified body is then extruded and sintered to obtain a cemented carbide material;
[0040] The cemented carbide powder includes the following raw materials by weight: 30-35 parts of tungsten carbide, 5-10 parts of niobium carbide, and 2-4 parts of nickel powder;
[0041] The ball milling liquid comprises the following raw materials in parts by weight: 10 to 15 parts of a bonding agent based on graphene modification and 8 to 12 parts of a lanthanum-regulated chitosan liquid.
[0042] The preparation method of the graphene-modified bonding agent of this embodiment is as follows:
[0043] S01: The graphene is first placed in a potassium permanganate solution with a mass fraction of 10% which is 3 to 5 times the total amount of the graphene, mixed thoroughly, then diluted with water, dried, and set aside;
[0044] S02: The graphene product of S01 and the nano-silicon dioxide modified liquid are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is washed with water, filtered and dried to obtain a graphene agent with continuous effect of silicon dioxide;
[0045] The preparation method of nano-silicon dioxide modified liquid is as follows:
[0046] First, the nano-silicon dioxide is added into a sodium silicate solution which is 3 to 5 times the total amount of the nano-silicon dioxide, and stirred and mixed thoroughly, and then filtered and dried to obtain the nano-silicon dioxide agent;
[0047] 2 to 5 parts of nano-silicon dioxide and 1 to 3 parts of stearic acid are added to 4 to 7 parts of phosphate buffer solution, and then 2 to 4 parts of sodium alginate are added and mixed to obtain a nano-silicon dioxide modified solution;
[0048] S03: The silica-modified graphene agent and the strengthening agent are mixed and ball-milled in a weight ratio of 5:3, with a ball-milling speed of 1000-1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a graphene-modified strengthening agent.
[0049] The stirring temperature of the stirring modification treatment in this embodiment is 48-52° C., the stirring speed is 550-750 r / min, and the stirring time is 1-2 h.
[0050] The mass fraction of the sodium silicate solution in this embodiment is 10-15%; the pH value of the phosphate buffer solution is 5.5.
[0051] The emphasizing agent of this embodiment includes the following raw materials in parts by weight:
[0052] 4-7 parts of nano strontium titanate, 1-3 parts of carboxymethyl cellulose, 5-8 parts of 10% sodium lignin sulfonate solution by mass, 1-2 parts of nano silica sol and 1-2 parts of 5% cobalt nitrate solution by mass.
[0053] The preparation method of the lanthanum-regulated chitosan solution of the present embodiment is as follows:
[0054] S101: irradiating the silicon carbide whisker with protons for 5 to 10 minutes at an irradiation power of 350 to 400 W, and obtaining irradiated silicon carbide whiskers after the irradiation is completed;
[0055] S102: chitosan is added to a sodium dodecylbenzene sulfonate solution at a weight ratio of 2:5, and then a lanthanum chloride solution with a total amount of 5-10% of the total amount of chitosan, an irradiated silicon carbide whisker with a total amount of 8-12% of the total amount of chitosan, and a silane coupling agent KH560 with a total amount of 2-5% of the total amount of chitosan are added, and the mixture is continued to be fully mixed to obtain a lanthanum-adjusted chitosan solution.
[0056] The mass fraction of the sodium dodecylbenzene sulfonate solution in this embodiment is 8-12%; the mass fraction of the lanthanum chloride solution is 2-5%.
[0057] The specific process of sintering improvement in this embodiment is as follows:
[0058] The sintering temperature is first raised to 70-75°C at a rate of 1-3°C / min, and then immersed in an yttrium nitrate solution for ultrasonic immersion treatment. After the immersion is completed, the sintering is taken out;
[0059] The sintering temperature is then raised to 450-480°C at a rate of 2-5°C / min and sintered for 5-10 minutes;
[0060] Then, the temperature is raised to 1050-1100°C at a rate of 8-12°C / min and sintering is continued for 25-30min;
[0061] Then increase the temperature to 1470-1490°C at a rate of 1-3°C / min, continue to keep warm for 10-15 minutes, and finally air cool to room temperature.
[0062] The immersion power of the ultrasonic immersion treatment in this embodiment is 400-450W, and the immersion time is 20-25min; the mass fraction of the yttrium nitrate solution is 2-5%.
[0063] A method for preparing a high wear-resistant cemented carbide material according to the present embodiment comprises the following steps:
[0064] Step 1, the raw materials of cemented carbide powder are mixed uniformly according to the proportion to obtain cemented carbide powder; then the cemented carbide powder and the ball milling liquid are ball milled at a weight ratio of (5-7):2, the ball milling speed is 1500r / min, the ball milling is performed for 2h, and after the ball milling is completed, the ball milling is washed with water and dried to form a ball milled modified body;
[0065] Step 2: Extruding the ball-milled modified body in a molding machine at a pressure of 100-120 MPa for 20-30 min to obtain a molded body, and finally sintering and improving the body to obtain the high wear-resistant cemented carbide material of the present invention.
[0066] Example 1
[0067] A high wear-resistant cemented carbide material of this embodiment is obtained by ball-milling a cemented carbide powder and a ball-milling liquid in a weight ratio of 5:2 to form a ball-milled modified body, and then extruding and sintering the ball-milled modified body to obtain a cemented carbide material;
[0068] The cemented carbide powder includes the following raw materials by weight: 30 parts of tungsten carbide, 5 parts of niobium carbide, and 2 parts of nickel powder;
[0069] The ball milling liquid comprises the following raw materials in parts by weight: 10 parts of a bonding agent based on graphene modification and 8 parts of a lanthanum-adjusted chitosan liquid.
[0070] The preparation method of the graphene-modified bonding agent of this embodiment is as follows:
[0071] S01: The graphene is first placed in a potassium permanganate solution with a mass fraction of 10% which is three times the total amount of the graphene, mixed thoroughly, then diluted with water, dried, and set aside;
[0072] S02: The graphene product of S01 and the nano-silicon dioxide modified liquid are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is washed with water, filtered and dried to obtain a graphene agent with continuous effect of silicon dioxide;
[0073] The preparation method of nano-silicon dioxide modified liquid is as follows:
[0074] First, add the nano-silicon dioxide into a sodium silicate solution which is 3 times the total amount of the nano-silicon dioxide, stir and mix thoroughly, then filter and dry to obtain the nano-silicon dioxide agent;
[0075] 2 parts of nano-silica and 1 part of stearic acid are added to 4 parts of phosphate buffer solution, and then 2 parts of sodium alginate are added and mixed to obtain a nano-silica modified solution;
[0076] S03: The silica-modified graphene agent and the strengthening agent are mixed and ball-milled in a weight ratio of 5:3, with a ball-milling speed of 1000 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a graphene-modified strengthening agent.
[0077] The stirring temperature of the stirring modification treatment in this embodiment is 48° C., the stirring speed is 550 r / min, and the stirring time is 1 h.
[0078] The mass fraction of the sodium silicate solution in this embodiment is 10%; the pH value of the phosphate buffer solution is 5.5.
[0079] The emphasizing agent of this embodiment includes the following raw materials in parts by weight:
[0080] 4 parts of nano-strontium titanate, 1 part of carboxymethyl cellulose, 5 parts of 10% by mass sodium lignin sulfonate solution, 1 part of nano-silica sol and 1 part of 5% by mass cobalt nitrate solution.
[0081] The preparation method of the lanthanum-regulated chitosan solution of the present embodiment is:
[0082] S101: irradiating the silicon carbide whisker with protons for 5 minutes at an irradiation power of 350 W, and obtaining irradiated silicon carbide whiskers after the irradiation is completed;
[0083] S102: chitosan is added to the sodium dodecylbenzene sulfonate solution at a weight ratio of 2:5, and then lanthanum chloride solution with a total amount of 5% of the total amount of chitosan, irradiated silicon carbide whiskers with a total amount of 8% of the total amount of chitosan, and silane coupling agent KH560 with a total amount of 2% of the total amount of chitosan are added, and the mixture is continued to be fully mixed to obtain a lanthanum-adjusted chitosan solution.
[0084] The mass fraction of the sodium dodecylbenzenesulfonate solution in this embodiment is 8%; the mass fraction of the lanthanum chloride solution is 2%.
[0085] The specific process of sintering improvement in this embodiment is as follows:
[0086] The sintering temperature is first raised to 70°C at a rate of 1°C / min, and then immersed in an yttrium nitrate solution for ultrasonic immersion treatment. After the immersion is completed, the sintering piece is taken out;
[0087] The sintering temperature was then raised to 450°C at a rate of 2°C / min and sintered for 5 min;
[0088] Then the temperature was raised to 1050°C at a rate of 8°C / min and sintering was continued for 25min;
[0089] Then increase the temperature to 1470℃ at a rate of 1℃ / min, continue to keep warm for 10 minutes, and finally air cool to room temperature.
[0090] The immersion power of the ultrasonic immersion treatment in this embodiment is 400 W, and the immersion time is 20 min; the mass fraction of the yttrium nitrate solution is 2%.
[0091] A method for preparing a high wear-resistant cemented carbide material according to the present embodiment comprises the following steps:
[0092] Step 1, the raw materials of cemented carbide powder are mixed uniformly according to the proportion to obtain cemented carbide powder; then the cemented carbide powder and the ball milling liquid are ball milled at a weight ratio of 5:2, the ball milling speed is 1500r / min, the ball milling is performed for 2h, and after the ball milling is completed, the ball milling is washed with water and dried to form a ball milled modified body;
[0093] Step 2: Extruding the ball-milled modified body in a molding machine at a pressure of 100 MPa for 20 min to obtain a molded body, and finally sintering and improving the body to obtain the high wear-resistant cemented carbide material of the present invention.
[0094] Example 2
[0095] A high wear-resistant cemented carbide material of this embodiment is obtained by ball-milling a cemented carbide powder and a ball-milling liquid in a weight ratio of 7:2 to form a ball-milled modified body, and then extruding and sintering the ball-milled modified body to obtain a cemented carbide material;
[0096] The cemented carbide powder includes the following raw materials by weight: 35 parts of tungsten carbide, 10 parts of niobium carbide, and 4 parts of nickel powder;
[0097] The ball milling liquid comprises the following raw materials in parts by weight: 15 parts of a bonding agent based on graphene modification and 12 parts of a lanthanum-adjusted chitosan liquid.
[0098] The preparation method of the graphene-modified bonding agent of this embodiment is as follows:
[0099] S01: The graphene is first placed in a potassium permanganate solution with a mass fraction of 10% which is 5 times the total amount of the graphene, mixed thoroughly, then diluted with water, dried, and set aside;
[0100] S02: The graphene product of S01 and the nano-silicon dioxide modified liquid are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is washed with water, filtered and dried to obtain a graphene agent with continuous effect of silicon dioxide;
[0101] The preparation method of nano-silicon dioxide modified liquid is as follows:
[0102] First, add the nano-silicon dioxide into a sodium silicate solution with a volume 5 times the total volume of the nano-silicon dioxide, stir and mix thoroughly, then filter and dry to obtain the nano-silicon dioxide agent;
[0103] 5 parts of nano-silica and 3 parts of stearic acid are added to 7 parts of phosphate buffer solution, and then 24 parts of sodium alginate are added and mixed to obtain a nano-silica modified solution;
[0104] S03: The silica-modified graphene agent and the strengthening agent are mixed and ball-milled in a weight ratio of 5:3, with a ball-milling speed of 1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a graphene-modified strengthening agent.
[0105] The stirring temperature of the stirring modification treatment in this embodiment is 52° C., the stirring speed is 750 r / min, and the stirring time is 2 h.
[0106] The mass fraction of the sodium silicate solution in this embodiment is 15%; the pH value of the phosphate buffer solution is 5.5.
[0107] The emphasizing agent of this embodiment includes the following raw materials in parts by weight:
[0108] 7 parts of nano strontium titanate, 3 parts of carboxymethyl cellulose, 8 parts of 10% by mass sodium lignin sulfonate solution, 2 parts of nano silica sol and 2 parts of 5% by mass cobalt nitrate solution.
[0109] The preparation method of the lanthanum-regulated chitosan solution of the present embodiment is:
[0110] S101: irradiating the silicon carbide whisker with protons for 10 minutes at an irradiation power of 400 W, and obtaining irradiated silicon carbide whiskers after the irradiation is completed;
[0111] S102: chitosan is added to the sodium dodecylbenzene sulfonate solution in a weight ratio of 2:5, and then 10% of the total amount of chitosan is added with lanthanum chloride solution, 12% of the total amount of chitosan is irradiated with silicon carbide whiskers, and 5% of the total amount of chitosan is added with silane coupling agent KH560, and the mixture is continued to be fully mixed to obtain a lanthanum-adjusted chitosan solution.
[0112] The mass fraction of the sodium dodecylbenzene sulfonate solution in this embodiment is 12%; the mass fraction of the lanthanum chloride solution is 5%.
[0113] The specific process of sintering improvement in this embodiment is as follows:
[0114] The sintering temperature is first raised to 75°C at a rate of 3°C / min, and then immersed in an yttrium nitrate solution for ultrasonic immersion treatment. After the immersion is completed, the sintering piece is taken out;
[0115] The sintering temperature was then raised to 480°C at a rate of 5°C / min and sintered for 10 min;
[0116] Then the temperature was raised to 1100°C at a rate of 12°C / min and sintering was continued for 30 min;
[0117] Then increase the temperature to 1490°C at a rate of 3°C / min, continue to keep warm for 15 minutes, and finally air cool to room temperature.
[0118] The immersion power of the ultrasonic immersion treatment in this embodiment is 450W, and the immersion time is 25 minutes; the mass fraction of the yttrium nitrate solution is 5%.
[0119] A method for preparing a high wear-resistant cemented carbide material according to the present embodiment comprises the following steps:
[0120] Step 1, the raw materials of cemented carbide powder are mixed uniformly according to the proportion to obtain cemented carbide powder; then the cemented carbide powder and the ball milling liquid are ball milled at a weight ratio of 7:2, the ball milling speed is 1500r / min, the ball milling is performed for 2h, and after the ball milling is completed, the ball milling is washed with water and dried to form a ball milled modified body;
[0121] Step 2: Extruding the ball-milled modified body in a molding machine at a pressure of 120 MPa for 30 min to obtain a molded body, and finally sintering and improving to obtain the high wear-resistant cemented carbide material of the present invention.
[0122] Example 3
[0123] A high wear-resistant cemented carbide material of this embodiment is obtained by ball-milling a cemented carbide powder and a ball-milling liquid in a weight ratio of 3:1 to form a ball-milled modified body, and then extruding and sintering the ball-milled modified body to obtain a cemented carbide material;
[0124] The cemented carbide powder includes the following raw materials by weight: 32.5 parts of tungsten carbide, 7.5 parts of niobium carbide, and 3 parts of nickel powder;
[0125] The ball milling liquid comprises the following raw materials in parts by weight: 12.5 parts of a bonding agent based on graphene modification and 10 parts of a lanthanum-adjusted chitosan liquid.
[0126] The preparation method of the graphene-modified bonding agent of this embodiment is as follows:
[0127] S01: The graphene is first placed in a potassium permanganate solution with a mass fraction of 10% which is 4 times the total amount of the graphene, mixed thoroughly, then diluted with water, dried, and set aside;
[0128] S02: The graphene product of S01 and the nano-silicon dioxide modified liquid are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is washed with water, filtered and dried to obtain a graphene agent with continuous effect of silicon dioxide;
[0129] The preparation method of nano-silicon dioxide modified liquid is as follows:
[0130] First, add the nano-silicon dioxide into a sodium silicate solution with a volume 4 times the total volume of the nano-silicon dioxide, stir and mix thoroughly, then filter and dry to obtain the nano-silicon dioxide agent;
[0131] 3.5 parts of nano-silica and 2 parts of stearic acid are added to 5.5 parts of phosphate buffer solution, and then 3 parts of sodium alginate are added and mixed to obtain a nano-silica modified solution;
[0132] S03: The silica-modified graphene agent and the strengthening agent are mixed and ball-milled in a weight ratio of 5:3, with a ball-milling speed of 1250 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a graphene-modified strengthening agent.
[0133] The stirring temperature of the stirring modification treatment in this embodiment is 50° C., the stirring speed is 600 r / min, and the stirring time is 1.5 h.
[0134] The mass fraction of the sodium silicate solution in this embodiment is 12.5%; the pH value of the phosphate buffer solution is 5.5.
[0135] The emphasizing agent of this embodiment includes the following raw materials in parts by weight:
[0136] 5.5 parts of nano-strontium titanate, 2 parts of carboxymethyl cellulose, 6.5 parts of 10% by mass sodium lignin sulfonate solution, 1.5 parts of nano-silica sol and 1.5 parts of 5% by mass cobalt nitrate solution.
[0137] The preparation method of the lanthanum-regulated chitosan solution of the present embodiment is:
[0138] S101: irradiating the silicon carbide whisker with protons for 7.5 minutes at an irradiation power of 375 W, and obtaining irradiated silicon carbide whiskers after the irradiation is completed;
[0139] S102: chitosan is added to the sodium dodecylbenzene sulfonate solution at a weight ratio of 2:5, and then lanthanum chloride solution with a total amount of 7.5% of chitosan, irradiated silicon carbide whiskers with a total amount of 10% of chitosan, and silane coupling agent KH560 with a total amount of 3.5% of chitosan are added, and the mixture is continued to be fully mixed to obtain a lanthanum-adjusted chitosan solution.
[0140] The mass fraction of the sodium dodecylbenzene sulfonate solution in this embodiment is 10%; the mass fraction of the lanthanum chloride solution is 3.5%.
[0141] The specific process of sintering improvement in this embodiment is as follows:
[0142] The sintering temperature is first raised to 72°C at a rate of 2°C / min, and then immersed in an yttrium nitrate solution for ultrasonic immersion treatment. After the immersion is completed, the sintering piece is taken out;
[0143] The sintering temperature was then raised to 465°C at a rate of 3.5°C / min and sintered for 7.5min;
[0144] Then the temperature was raised to 1075°C at a rate of 10°C / min and sintering was continued for 28 min;
[0145] Then increase the temperature to 1480°C at a rate of 2°C / min, continue to keep warm for 12.5 minutes, and finally air cool to room temperature.
[0146] The immersion power of the ultrasonic immersion treatment in this embodiment is 425W, and the immersion time is 22.5min; the mass fraction of the yttrium nitrate solution is 3.5%.
[0147] A method for preparing a high wear-resistant cemented carbide material according to the present embodiment comprises the following steps:
[0148] Step 1, the raw materials of cemented carbide powder are mixed uniformly according to the proportion to obtain cemented carbide powder; then the cemented carbide powder and the ball milling liquid are ball milled at a weight ratio of 3:1, the ball milling speed is 1500r / min, the ball milling is performed for 2h, and after the ball milling is completed, the ball milling is washed with water and dried to form a ball milled modified body;
[0149] Step 2: Extruding the ball-milled modified body in a molding machine at a pressure of 110 MPa for 25 min to obtain a molded body, and finally sintering and improving the body to obtain the high wear-resistant cemented carbide material of the present invention.
[0150] Comparative Example 1
[0151] The difference from Example 3 is that no ball milling liquid treatment is used.
[0152] Comparative Example 2
[0153] Different from Example 3, no graphene-modified bonding agent was added in the preparation of the ball milling solution.
[0154] Comparative Example 3
[0155] The difference from Example 3 is that the nano-silicon dioxide modifying liquid treatment is not used in the preparation of the graphene-modified connecting agent.
[0156] Comparative Example 4
[0157] The difference from Example 3 is that no nano-silica agent is added in the preparation of the nano-silica modified liquid.
[0158] Comparative Example 5
[0159] The difference from Example 3 is that no stressing agent treatment is used in the preparation of the graphene-modified bonding agent.
[0160] Comparative Example 6
[0161] The difference from Example 3 is that the lanthanum-adjusted chitosan solution is replaced by deionized water.
[0162] Comparative Example 7
[0163] The difference from Example 3 is that no irradiated silicon carbide whiskers are added in the preparation of the lanthanum-regulated chitosan solution.
[0164] Comparative Example 8
[0165] The difference from Example 3 is that no lanthanum chloride solution and silane coupling agent KH560 were added in the preparation of the lanthanum-adjusted chitosan solution.
[0166] Comparative Example 9
[0167] The difference from Example 3 is that the ultrasonic immersion treatment in the yttrium nitrate solution is not used in the sintering improvement treatment.
[0168] Comparative Example 10
[0169] The difference from Example 3 is that the specific process of sintering improvement is different
[0170] The sintering temperature is first raised to 72°C at a rate of 2°C / min, and then immersed in an yttrium nitrate solution for ultrasonic immersion treatment. After the immersion is completed, the sintering piece is taken out;
[0171] Then, the temperature is raised to 1480°C at a rate of 10°C / min, sintering is continued for 50 minutes, and finally air-cooled to room temperature.
[0172] The products of Examples 1-3 and Comparative Examples 1-10 were tested for wear resistance and fracture toughness under normal conditions, and the products were placed in 2% hydrochloric acid for 24 hours, and then placed in a hot and cold shock chamber, the test temperature was reduced to -40°C, and placed for 2 hours, and then after 5 minutes, the test temperature was raised to 90°C and placed for 2 hours, and the above steps were repeated 5 times;
[0173] Wear resistance test: the test product is processed into a cutting tool to cut 42CrMo steel at a cutting speed of 250m / min, a cutting amount of 2mm, and a feed rate of 0.1mm / revolution. The processing length completed when the cutting tool tip wear reaches 0.1mm is used as the evaluation standard, unit: m;
[0174] The product's wear resistance and fracture toughness were tested under hot and cold shock and acid corrosion resistance conditions. The test results are as follows;
[0175]
[0176]
[0177] It is concluded from Examples 1-3 and Comparative Examples 1-10 that
[0178] The product of Example 3 of the present invention has excellent fracture toughness performance and significant wear resistance under normal conditions. At the same time, the fracture toughness and wear resistance are improved in a coordinated manner. The product has significant performance stability under hot and cold shock and acid corrosion resistance conditions.
[0179] It can be seen from Comparative Examples 1-2, Comparative Example 6 and Example 3 that the performance of the product deteriorated significantly when the ball milling solution was not used for treatment. At the same time, the graphene-modified connecting agent and the lanthanum-adjusted chitosan solution were not added in the preparation of the ball milling solution, and deionized water was used instead. The performance of the product deteriorated significantly. The ball milling solution obtained by co-mixing the graphene-modified connecting agent and the lanthanum-adjusted chitosan solution was used for treatment, and the performance effect of the product was significant.
[0180] It can be seen from Comparative Examples 3-5, Comparative Examples 7-8 and Example 3 that the performance of the product also shows a trend of deterioration when the nano-silicon dioxide modifying liquid is not used for the preparation of the graphene-modified connecting agent, the nano-silicon dioxide agent is not added in the preparation of the nano-silicon dioxide modifying liquid, and the emphasizing agent is not used in the preparation of the graphene-modified connecting agent. In particular, the performance of the product deteriorates significantly when the emphasizing agent is not used. The performance of the product also shows a trend of deterioration when the irradiated silicon carbide whiskers are not added in the preparation of the lanthanum-regulated chitosan solution, the lanthanum chloride solution and the silane coupling agent KH560 are not added in the preparation of the lanthanum-regulated chitosan solution. Only the lanthanum-regulated chitosan solution obtained by the method of the present invention and the graphene-modified connecting agent have the most significant performance effect of the product, and the use of other methods instead is not as obvious as the effect of the present invention.
[0181] It can be seen from Comparative Examples 9-10 and Example 3 that the sintering improvement treatment does not use ultrasonic immersion treatment in yttrium nitrate solution, and the specific processes of sintering improvement are different, and the performance of the product also shows a trend of deterioration. Only when the specific sintering improvement treatment of the present invention is used, the performance effect of the product is most significant.
[0182] Since the enhancer has a significant effect on the performance of the product, further research is conducted on this:
[0183] Experimental Example 1
[0184] The only difference from Example 3 is that no nano strontium titanate is added to the emphasizing agent.
[0185] Experimental Example 2
[0186] The only difference from Example 3 is that no cobalt nitrate solution is added to the emphasizing agent.
[0187] Experimental Example 3
[0188] The only difference from Example 3 is that no nano silica sol is added to the emphasizing agent.
[0189] Experimental Example 4
[0190] The only difference from Example 3 is that the sodium lignin sulfonate solution in the emphasizing agent is replaced by deionized water.
[0191]
[0192]
[0193] It can be seen from Experimental Examples 1-4 that when nano strontium titanate is not added to the emphasizing agent, the performance of the product is most affected by the emphasizing agent, followed by the fact that cobalt nitrate solution is not added, and when nano silica sol is not added to the emphasizing agent and deionized water is used instead of sodium lignin sulfonate solution, the performance of the product tends to deteriorate. The specific raw materials of the present invention are used in the preparation of the emphasizing agent, and the performance effect of the product is the most significant. The effect of the present invention cannot be achieved by using other raw materials instead.
[0194] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0195] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A high wear-resistant cemented carbide material, characterized in that: The cemented carbide material is a cemented carbide powder and a ball milling liquid in a weight ratio of (5-7):2, and is subjected to ball milling modification to form a ball milling modified body. The ball milling modified body is then extruded, sintered, and improved to obtain a cemented carbide material. The cemented carbide powder includes the following raw materials by weight: 30-35 parts of tungsten carbide, 5-10 parts of niobium carbide, and 2-4 parts of nickel powder; The ball milling liquid comprises the following raw materials in parts by weight: 10 to 15 parts of a graphene-modified bonding agent and 8 to 12 parts of a lanthanum-adjusted chitosan liquid; the preparation method of the graphene-modified bonding agent is as follows: S01: The graphene is first placed in a 10% potassium permanganate solution with a mass fraction of 3 to 5 times the total amount of graphene and mixed thoroughly, then washed with water, dried, and set aside; S02: The graphene product of S01 and the nano-silicon dioxide modified liquid are stirred and modified in a weight ratio of 2:
5. After the stirring is completed, the mixture is washed with water, filtered and dried to obtain a graphene agent with continuous effect of silicon dioxide; The preparation method of nano-silicon dioxide modified liquid is as follows: First, the nano-silicon dioxide is added into a sodium silicate solution which is 3 to 5 times the total amount of the nano-silicon dioxide, and stirred and mixed thoroughly, and then filtered and dried to obtain the nano-silicon dioxide agent; 2 to 5 parts of nano-silicon dioxide and 1 to 3 parts of stearic acid are added to 4 to 7 parts of phosphate buffer solution, and then 2 to 4 parts of sodium alginate are added and mixed to obtain a nano-silicon dioxide modified solution; S03: The silica-modified graphene agent and the strengthening agent are mixed and ball-milled in a weight ratio of 5:3, with a ball-milling speed of 1000-1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a graphene-modified strengthening agent.
2. A high wear-resistant cemented carbide material according to claim 1, characterized in that: The stirring temperature of the stirring modification treatment is 48-52° C., the stirring speed is 550-750 r / min, and the stirring time is 1-2 h.
3. A high wear-resistant cemented carbide material according to claim 1, characterized in that: The mass fraction of the sodium silicate solution is 10-15%; the pH value of the phosphate buffer solution is 5.
5.
4. A high wear-resistant cemented carbide material according to claim 1, characterized in that: The emphasizing agent comprises the following raw materials in parts by weight: 4-7 parts of nano-strontium titanate, 1-3 parts of carboxymethyl cellulose, 5-8 parts of 10% by mass sodium lignin sulfonate solution, 1-2 parts of nano-silica sol and 1-2 parts of 5% by mass cobalt nitrate solution.
5. The high wear-resistant cemented carbide material according to claim 1, characterized in that: The preparation method of the lanthanum-regulated chitosan solution is: S101: irradiating the silicon carbide whisker with protons for 5 to 10 minutes at an irradiation power of 350 to 400 W, and obtaining irradiated silicon carbide whiskers after the irradiation is completed; S102: chitosan is added to a sodium dodecylbenzene sulfonate solution at a weight ratio of 2:5, and then 5-10% of a lanthanum chloride solution, 8-12% of an irradiated silicon carbide whisker, and 2-5% of a silane coupling agent KH560 are added to the total amount of chitosan, and the mixture is continued to be fully mixed to obtain a lanthanum-adjusted chitosan solution.
6. A high wear-resistant cemented carbide material according to claim 5, characterized in that: The mass fraction of the sodium dodecylbenzene sulfonate solution is 8-12%; the mass fraction of the lanthanum chloride solution is 2-5%.
7. A high wear-resistant cemented carbide material according to claim 1, characterized in that: The specific process of the sintering improvement is: The sintering temperature is first raised to 70-75°C at a rate of 1-3°C / min, and then immersed in an yttrium nitrate solution for ultrasonic immersion treatment. After the immersion is completed, the sintering is taken out; The sintering temperature is then raised to 450-480°C at a rate of 2-5°C / min and sintered for 5-10 minutes; Then, the temperature is raised to 1050-1100°C at a rate of 8-12°C / min and sintering is continued for 25-30min; Then increase the temperature to 1470-1490°C at a rate of 1-3°C / min, continue to keep warm for 10-15 minutes, and finally air cool to room temperature.
8. A high wear-resistant cemented carbide material according to claim 7, characterized in that: The immersion power of the ultrasonic immersion treatment is 400-450W, and the immersion time is 20-25min; the mass fraction of the yttrium nitrate solution is 2-5%.
9. The method for preparing a high wear-resistant cemented carbide material according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1, the raw materials of cemented carbide powder are mixed uniformly according to the proportion to obtain cemented carbide powder; then the cemented carbide powder and the ball milling liquid are ball milled at a weight ratio of (5-7):2, the ball milling speed is 1500r / min, the ball milling is performed for 2h, and after the ball milling is completed, the ball milling is washed with water and dried to form a ball milled modified body; Step 2: Extruding the ball-milled modified body in a molding machine at a pressure of 100-120 MPa for 20-30 min to obtain a molded body, and finally sintering to obtain a highly wear-resistant cemented carbide material.
Citation Information
Patent Citations
Hard alloy cutter material and preparation method thereof
CN117401977A